Efek Hepatoprotektif Bit Merah (Beta vulgaris L) Organik terhadap Abnormalitas Faal Hepar Akibat Paparan Pestisida - Ikawati, Kartika; Widodo, Agus (Poltekkes Kemenkes Tanjung Karang, 2021)
Pesticide exposure causes hepatic parenchymal cell damage and impaired hepatic membrane permeability. Organic red beets contain high levels of flavonoids, betanin, and polyphenols. The phytochemical compounds in beetroot are anti-inflammatory, antioxidant, and antihepatotoxicity. The purpose of this study was to determine the hepatoprotective effect of organic beetroot (Beta vulgaris L) on hepar physiological abnormalities due to exposure to pesticides. This type of research is an experiment with Post Test Only Randomized Control Group Design. The study population was male Wistar rats aged 2-3 months with a weight of 150-200g. The sampling technique was randomly assigned to 30 rats were divided into 6 groups. Beetroot ethanol extract intake and pesticide exposure were observed for 14 days. Liver physiological abnormalities were measured based on the levels of the enzyme cholinesterase, Gamma GT, SGOT, and SGPT. Measurement of enzymes using the IFCC method, using Stardust MC15 and Humalyzer spectrophotometer. Data analysis using Anova test. There was a hepar physiological abnormality after pesticide exposure which was indicated by a significant decrease in the cholinesterase enzyme (p-value=0,000) and a significant increase in the Gamma GT, SGOT, and SGPT enzymes (p-value=0,000). The intake of organic beetroot ethanol extract (Beta vulgaris L) significantly increased the cholinesterase enzyme back (p-value=0,000) and significantly decreased the Gamma GT, SGOT, and SGPT enzymes (p-value=0,000), approaching normal levels at a dose of 400mg/kgBW. Organic red beetroot (Beta vulgaris L) has a hepatoprotective effect on hepar physiological abnormalities due to exposure to pesticides.